Like, Share, Improve: Student Feedback on Northwestern University’s Student Services - Eric Santos Parilla (Education Policy and Development, 2026)
This study examines the effects of service quality dimensions on student satisfaction and institutional reputation at Northwestern University in the Philippines, using the SERVQUAL framework. A mixed-methods research design was employed to provide a comprehensive assessment of student service experiences. Quantitative data were gathered through a structured Likert-scale survey administered to students across different colleges, and analyzed using descriptive statistics, ANOVA, Pearson correlation, and multiple linear regression to determine group differences and predictive relationships between service quality and institutional reputation. To complement the survey findings, qualitative data were obtained through document analysis of student feedback submitted via the university’s suggestion box system and compiled by the Quality Assurance Office. These qualitative inputs were thematically analyzed to identify recurring service concerns, commendations, and areas requiring improvement. Results indicate that tangibility, assurance, and empathy significantly predict institutional reputation, while reliability and responsiveness show limited influence. Qualitative findings further reveal persistent issues related to infrastructure maintenance, staff professionalism, service accessibility, and digital connectivity, providing contextual depth to the quantitative results. The study underscores the importance of integrating student feedback into institutional decision-making and highlights the need for strategic investments in facilities, human interaction, and student-centered services. These findings offer empirical and practical insights for higher education policy formulation, service enhancement, and institutional branding within the Philippine context and similar settings.